Kebijakan Pelayanan Publik Dalam Penyelenggaraan Layanan Pertanahan Akhir Pekan (PELATARAN) - Budi Arif Muslikan (Faculty of Law, Diponegoro University, 2023)
Pelataran is a form of public service at the land office which provides service priority counters and land service programs on weekends, namely giving the public the opportunity to apply for the issuance of land certificates, especially on Saturdays and Sundays. Applicants who receive Pelataran services are specifically intended for landowners without intermediaries or without power of attorney. The purpose of applying for a land certificate at the land office is to obtain strong evidence of land ownership and provide legal certainty for the owner. Therefore, the aim of this research is to analyze the role and quality of the Pelataran services provided by the Demak district land office. Descriptive analysis is used to see the relationship and linkages between theory and the results of analysis in the field. The research object is the Demak district land office with research subjects namely land office employees and the people who access the Pelataran program. The results of the study show that the Pelataran program is effective in providing outreach and easy access for the community on weekends in submitting land certificate applications. The role of the Pelataran program has helped minimize the occurrence of administrative defects and acts of administrative procedural irregularities, illegal levies, and provided time effectiveness in processing land titles to the people of Demak district. Then, the Demak district land office also provides public complaints regarding the Pelataran program so as to provide information disclosure and service improvement. The Pelataran registration counter is also a priority for people who come on Saturdays and Sundays and also apply digital services.